Mathematics

Question

Simplify the expression. 8 ( 5 + t ) - 6 ( t + 1)

2 Answer

  • First step you should do when simplifying this expression is by distributing it..
    =(8)(5)+(8)(t)+(−6)(t)+(−6)(1)
    =40+8t+6t+−6
    Second is to C
    ombine Like Terms..
    =40+8t+6t+−6
    =(8t+6t)+(40+−6)
    Then you should get the answer:
    =2t+34

    Good luck and Happy new years!! ^-^
  • First distribute into parentheses.
    40 + 8t - 6t - 6
    Now add like terms
    40 - 6= 34
    8t - 6t= 2t
    Answer is 2t + 34
NEWS TODAY